A Sugar Estate, Trinidad - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2009)
A picture of East Indian labourers standing amidst the sugar cane stalks.
Colour: Black and White; Style: Portrait; Other: Unbordered, Undivided
Keywords: Trinidad and Tobago; Postcards; Sugarcane industry; Sugarcane; Working class; East Indians